Why are boys falling behind? Explaining gender gaps in school attainment in Sri Lanka. (June 2021) - Himaz, Rozana; Aturupane, Harsha
Highlights: Attainment in school and enrollment in post-compulsory education are lower for males compared to females in Sri Lanka. Implicit biases favour girls with parental aspirations and teacher attitudes higher for girls than boys. Gaps in maths scores at age 12 are explained by differences in returns to endowments rather than differences in endowments. Earnings foregone are more significant in males' decision to enroll compared to females', even when controlled for wealth. Positive discrimination of males in the labour market may explain poor attainment at the school level. Abstract: An increasingly common trend in developed countries and middle income countries such as Thailand, South Africa, Malaysia, Indonesia and Sri Lanka is that females outperform males in terms of attainment at school and enrollment in higher education, on average. Surprisingly, in countries such as Sri Lanka and Thailand, households also seem to allocate significantly higher resources towards girls' education rather than boys' (Himaz, 2010; Wongmonta & Glewwe, 2017). This paper looks at attainment in mathematics among a sample of 12 year olds in Sri Lanka and uses decomposition analysis to see to what extent parental aspirations and teacher attitudes, inter alia, can explain gender differentials disfavoring boys. The paper finds that although teacher attitudes and parental aspirations are significantly lower for boys, these factors -as we measure them- do not sufficiently explain the attainment gap. Much of the gap remains 'unexplained' and is due to differences in returns to endowments. The paper argues that positive discrimination of men in the labor market and bottle necks in higher-education may be important in understanding the unexplained component. This emphasizes the need to look beyond school level interventions to address the issue of gender imbalances in attainment.